Working Through Work Release: An Analysis of Factors Associated with the Successful Completion of Work Release - Rukus, Joseph (American journal of criminal justice, 2016)
In line with reentry and life course research that has shown increases in desistance for individuals connected with employment, work release programming attempts to achieve desistance from crime by linking criminal offenders to the labor market while in the correctional system. Recent research has speculated that the completion of rigorous employment programming may serve as a signal to employers that criminal careers have ceased and the offenders are employable. Therefore, it is important to understand factors associated with successful program completion. This study utilizes a sample of jail-based work release participants to explore factors correlated with program completion. Consistent with prior research, we find that offenders who are older, Caucasian, and employed at time of arrest are more likely to complete the program and that minority participants and those with prior mental health treatment are less likely to complete the program.